Multiplication of Logarithms

Multiplication of Logarithms

Reminder - Logarithms

Reminder of the loglog definition?
logax=blog_a⁡x=b
X=abX=a^b
Where:
aa is the base of the log
bb is the exponent we raise the log base to in order to obtain the number inside the log.
XX is what appears inside the log, it can also appear in parentheses.

Multiplication of logarithms with the same base

According to the rule
loga(xy)=logax+logaylog_a⁡(x\cdot y)=log_a⁡x+log_a⁡y

When the content of the log is a multiplication expression, we can split it into an addition expression – 22 logs will have the same base.
The first log will be with the first term in the multiplication and the second log will be with the second term in the multiplication.

A multiplication exercise can be converted to an addition exercise and an addition exercise to a multiplication exercise with one log according to the rule as long as the base is the same.

Multiplication of Logarithms

Multiplication of logarithms with the same base

In order to solve perform the multiplication of logarithms, you need to know the following rule:
loga(xy)=logax+logaylog_a⁡(x\cdot y)=log_a⁡x+log_a⁡y
When there is multiplication inside the log, we can split the log into an addition problem with the same base where one log will have the content of one of the factors and the second log will have the content of the second factor.
You can convert the multiplication problem to an addition problem and an addition problem to a multiplication problem with one log according to the rule as long as the base is the same.

Let's look at an example:
log4(6416)=log_4⁡(64\cdot16)=
We have an expression with a logarithm containing a multiplication operation. If we were to multiply what's inside of the parentheses, we would obtain something like this:
log4(1024)=log_4⁡(1024)=

Of course, thanks to the rule, we can solve this exercise in a much easier and faster way.
We just need to split the exercise into an addition exercise with 22 identical bases - in this exercise the base is 44.
It should look like this:
log4(6416)=log464+log416log_4⁡(64\cdot16)=log_4⁡64+log_4⁡16

Now we can solve the exercise with greater ease!

Reminder -
The definition of a logarithm is:
logax=blog_a⁡x=b
X=abX=a^b
Where:
aa is the base of the logarithm
XX is what appears inside the logarithm. It can also appear in parentheses.
bb is the exponent to which we raise the base of the logarithm to obtain the number inside the logarithm.

And so we ask ourselves - to what power do we need to raise 44 to in order to obtain 6464? The answer is 33.
And to what power do we need to raise 44 to in order to obtain 1616? The answer is 22.
We obtained the following:
log464+log416=3+2=5log_4⁡64+log_4⁡16=3+2=5

Let's solve another exercise!
log6(36216)=log_6⁡(36\cdot216)=

Solution:
To solve this exercise, we'll use the rule we learned about multiplying logarithms.
We can split the exercise into an addition exercise where the base is identical and equals 66.
As follows:
log636+log6216=log_6⁡36+log_6⁡216=
Now we can solve the problem more easily.
We know that in order to obtain 3636 we need to raise 66 to the power of 22 therefore
log636=2log_6⁡36=2
and in order to obtain 216216 we need to raise 66 to the power of 33 therefore
log6216=3log_6⁡216=3
Let's substitute the data into the exercise as follows:
2+3=52+3=5
55 is the final answer.

Let's proceed to another exercise!
\(log_6⁡2+log_6⁡18=\

Pay attention! At first glance, this exercise appears to be an addition of logarithms with the same base... however! We are using the rule we learned about multiplying logarithms!

Solution Method:
Let's first try to solve the exercise without the rule -
log62=log_6⁡2=
If we think about which power we need to raise 66 to in order to obtain 22... we encounter a problem. This is not an intuitive solution
The again encounter the same problem for log618=log_6⁡18=
Which power do we need to raise 66 to in order to obtain 1818? Also a good question..
Therefore, we use the rule that states we can multiply the 22 log contents with the same base. As seen below:

log62+log618=log6(218)log_6⁡2+log_6⁡18=log_6⁡(2\cdot18)
=log636=log_6⁡36
How wonderful! We now understand that in order to reach 3636 we need to raise 66 to the power of 22!
Therefore the solution is 22. This is the final answer.

What did we learn? The multiplication rule we learned follows the commutative property.
It works on both sides - you can convert a multiplication expression into an addition expression, and an addition expression can be converted into a single log with multiplied content.
However - only if the base is identical.

Note - If there is multiplication of logarithms with different bases, you can try to convert the log base according to the rules you learned.

Join Over 30,000 Students Excelling in Math!
Endless Practice, Expert Guidance - Elevate Your Math Skills Today